The quest for the “religious originality” in Gaul in the imperial period - Bina, Tatiana (Romanitas - Revista de Estudos Grecolatinos, 2015)
The debate on “Romanization”, so common since the 70’s, may have been became “naturalized” as a descriptive discourse of the provincial realities, but effectively what sustained it may have not been properly sized historiographically: non-Roman archaeological evidence or Roman but local changes that have been found and highlighted from the second quarter of the century XX. The article tries to make an analysis of the theoretical discussions that created these topoi and present two examples of archaeological evidence to attest the existence of a religious originality in Gaul Roman in the imperial period.